'To Shock the Conscience': Rhetoric in Death Penalty Judgements of the Supreme Court of India. Issue 4 (4th July 2019) - Saikumar, Rajgopal
Abstract: The dominant paradigm in scholarship on death penalty law in India is doctrinal and empirical. There is an equally indispensable need for a third approach that focuses on the rhetoric of and in death penalty judgements. In the first part of the paper I argue why such an approach is necessary, and in the second part I instantiate this by a close reading of narrative techniques and rhetorical devices deployed in two recent Supreme Court judgements. I show the use of antirrhetic speech, ekphrasis and the 'reality effect' woven into the narrative of the taboo on incest, peopled with characters such as 'diabolical monsters' plotting 'sinister designs'. Embedded in these narratives are judges who see themselves as reconstituting a community on the verge of breakdown. In this circular operation, monsters are linguistically created, and the monstrosity of the criminal is then used as a justification for death. Yet such a monster cannot be a wholly non-human figure because intent is necessary for fixing legal responsibility.